A Study of Socio-Cultural Aspects of Kada To Minaa Toraja Discourse in the Students’ Character Building - Elim Trika Sudarsi; Nilma Taula’bi’; Markus Deli Girik Allo; Eka Prabawati Rum (Master Program in Linguistics, Diponegoro University, 2021)
This study aims to know the socio-cultural aspects of the discourse kada to minaa Toraja in the formation of the character of learners. This research method is qualitative with an ethnographic design. The data analysis technique in this study is Ethnographic Research Cycle. The results of this study showed that the socio-cultural aspects of kada to minaa Toraja discourse in the formation of the character of learners are: First, the aspect of politeness value in kada to minaa, namely Mekatabe' londong lako to disa'bu' gayang ma'pampang ma'paran-paran. Second, the religious aspect of kada to minaa